Integration of Vegetables into Maize-Based Farming Systems in Babati: Cost-Benefit Analyses on Integrated Intercropping Systems from Demo Plots for Adaptability Testing by AVRDC - World Vegetable Center; Ministry of Agriculture Food Security and Cooperatives (International Food Policy Research Institute, 2017)
Project title: Research in Sustainable Intensification in the Sub-Humid Maize-Based Cropping Systems of Babati, Tanzania. Project abstract: We undertake a profitability analysis of the incremental changes in existing practices by farmers in comparison with standard farmer practices so as to enable farmers to visualize the economic benefits of the proposed technologies including vegetable-cereal intercropping and crop rotation trials for new technology adoption. Project website: http://africa-rising.net